Synthesis of 1-phenyl-3, 4-dihydropyrimidine-2(1H)-ones derivatives under solvent free condition and their antimicrobial activity - Akhter, K; Jahan, K; Halim, ME; Shefa, S; Rifat, S; Khan, KR; Ahmed, SM; Romman, UKR (Bangladesh Journal of Scientific and Industrial Research, 2019)
We report herein the use of nickel nitrate hexahydrate [Ni(NO3)2.6H2O] as a new catalyst for the one-pot Biginelli like reaction coupling of 1-phenyl thiourea, ethyl acetoacetate and aromatic aldehydes to afford the corresponding 1-phenyl-3,4-dihydropyrimidin-2(1H)-thiones under solvent free condition to avoid the usage of hazardous organic solvents. The synthesized compounds were evaluated for their antimicrobial activity by KIRBY-BAUER disk diffusion method. Most of the compounds showed good to moderate antimicrobial activity. Bangladesh J. Sci. Ind. Res.54(1), 47-54, 2019